Host range expansion of wheat stem rust resistance genes into barley - Md Hatta, Muhammad Asyraf; Johnson, Ryan; Matny, Oadi; Smedley, Mark A.; Yu, Guotai; Chakraborty, Soma; Bhatt, Dhara; Xia, Xiaodi; Arora, Sanu; Steuernagel, Burkhard; Richardson, Terese; Mago, Rohit; et al. (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
In the last 20 years, stem rust caused by the fungus Puccinia graminis f. sp. tritici (Pgt), has re-emerged as a major threat to wheat and barley cultivation in Africa and Europe. In contrast to wheat with 82 designated stem rust (Sr) resistance genes, barley’s genetic variation for stem rust resistance is very narrow with only seven resistance genes genetically identified. Of these, only one locus consisting of two genes is effective against Ug99, a strain of Pgt which emerged in Uganda in 1999 and has since spread to much of East Africa and parts of the Middle East. The objective of this study was to assess the functionality, in barley, of cloned wheat Sr genes effective against Ug99. Sr22, Sr33, Sr35 and Sr45 were transformed into barley cv. Golden Promise using Agrobacterium-mediated transformation. All four genes were found to confer effective stem rust resistance. The barley transgenics remained susceptible to the barley leaf rust pathogen Puccinia hordei, indicating that the resistance conferred by these wheat Sr genes was specific for Pgt. Cloned Sr genes from wheat are therefore a potential source of resistance against wheat stem rust in barley.